Kepatuhan Penggunaan Alat Pelindung Diri pada Petugas Kesehatan di Rumah Sakit melalui Pengembangan Metode Human Factor Design: Kajian Literatur - Istigfari, Salsabila Nur; Dwiantoro, Luky (Holistic Nursing and Health Science, 2022)
Background: PPE noncompliance by health workers found in many hospitals due to knowledge, facilities, and environmental factors, increases the risk of nosocomial infections. Personal protective equipment (PPE) compliance for health workers is an important aspec of infection control and prevention. The purpose of this study is to identify the developments of human factor design’s method and its effectiveness in increasing PPE compliance for health workers based on a literature review.Methods: The method used in this paper is a literature review. Data was taken through journals obtained by searching Garuda Ristekdikti, Google Scholar, and Science Direct. Articles selected based on some criteria including: topics of PPE compliance among health workers at hospital, publication year 2012-2021, full text articles, and written in Indonesian or English.Results: Literature review of 6 articles, show that human factor design is one of the standard interventions that can be applied to improve the quality of human resources by considering 3 system domains including physical, cognitive, dan organizational. Increasing standard precautions and transmission through poster media, comprehensive education with edutainment videos, and controling by supervision can provide effectiveness in increasing PPE compliance for health workers in hospitals.Conclusion: It can be concluded that compliance with the use of PPE for health workers can be improved through human factor design program.